2014
DOI: 10.5194/tc-8-2381-2014
|View full text |Cite
|
Sign up to set email alerts
|

Elevation dependency of mountain snow depth

Abstract: Abstract. Elevation strongly affects quantity and distribution patterns of precipitation and snow. Positive elevation gradients were identified by many studies, usually based on data from sparse precipitation stations or snow depth measurements. We present a systematic evaluation of the elevationsnow depth relationship. We analyse areal snow depth data obtained by remote sensing for seven mountain sites near to the time of the maximum seasonal snow accumulation. Snow depths were averaged to 100 m elevation ban… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 66 publications
13
89
0
Order By: Relevance
“…10). This was also found by lidar measurements carried out in the same catchment (Helfricht et al, 2012) as well as in several catchments in Switzerland (Grünewald et al, 2014). By applying a simple hydrological model that uses elevation bands instead of raster cells to a variety of other catchments in the Alps, Frey (2015) could identify this elevation range, too.…”
Section: Transferability To Other Catchmentsmentioning
confidence: 68%
“…10). This was also found by lidar measurements carried out in the same catchment (Helfricht et al, 2012) as well as in several catchments in Switzerland (Grünewald et al, 2014). By applying a simple hydrological model that uses elevation bands instead of raster cells to a variety of other catchments in the Alps, Frey (2015) could identify this elevation range, too.…”
Section: Transferability To Other Catchmentsmentioning
confidence: 68%
“…Topography is an important factor affecting climatology of snow depth and the main reason accounting for snow depth data inhomogeneity Lehning, 2011, 2013;Grünewald et al, 2014). To explore the effects of complex terrain on snow depth over Eurasia, we conducted a linear regression analysis of long-term mean annual snow depth with latitude, elevation, and continentality (Fig.…”
Section: Impact Of Topography On Snow Depthmentioning
confidence: 99%
“…Ye et al (1998) and Kitaev et al (2005) showed that higher air temperatures caused an increase in snowfall in winter from 1936 through 1995, and thus greater snow depth was observed in northern Eurasia. Snow depth distribution and variation are controlled by terrain (i.e., elevation, slope, aspect, and roughness) and vegetation Grünewald et al, 2014;Revuelto et al, 2014;Rees et al, 2014;Dickerson-Lange et al, 2015). Snow depth is closely related to synoptic-scale atmospheric circulation indices such as the North Atlantic OscillationArctic Oscillation (NAO/AO).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated snow depth varied from 1.16 to 4.34 m in the north flank, 1.68 to 2.94 m in the south flank and 0.87 to 2.61 m in the central glacier during the study period. More precipitation (snow) at higher altitude could be attributed to the orographic effect, which results in an increase in snow accumulation with elevation [43][44][45][46][47][48] . Correlation coefficients of accumulated snow depth on the north flank, south flank and central glacier with the altitude were found to be 0.78, 0.84 and 0.57 respectively (significant at 1% significance level).…”
Section: Uncertainties In Snow Accumulation On Glaciermentioning
confidence: 99%